THE ROLE OF EDUCATORS IN PREVENTING PSYCHOLOGICAL VIOLENCE IN GRADE 1 CHILDREN - Mulyati, Mulyati; Patilima, Hamid (Journal of Early Childhood Education (JECE), 2022)
The problem that occurs at this time is that the role of education is still not realized as its function optimally in overcoming violence prevention in the learning environment for elementary school children. The purpose of this study was to determine the role of educators in preventing psychological violence in elementary school children. The research methodology uses qualitative data collection methods using observation and relevant documentation. The research subjects were conducted on 25 elementary school teachers by providing debriefing and training and assisted by two master's students. Data analysis techniques use the approach from Miles and Huberman. The results show that the role of educators should be optimal in facilitating learning assistance for children. Schools as educational institutions can submit procedural SOPs made in the form of written rules as a solution to minimize the occurrence of ongoing child psychological distress. The role of the teacher during the learning process can provide direction through positive instructions to children. As well as collaboration between school principals, teachers and parents it is important to do that can be used as an internal monitoring system, so that children can feel that they are being watched, protected and given attention.